Arendt: ação, história e educação - Santos Junior, Nei Jairo Fonseca dos (Universidade do Vale do Rio dos Sinos, 2008)
The propose of this lecture is to rescue, in the writings, her perspective about the sense and the meaning of the human action in the context of the historical understanding of the totalitarian regime and of the crisis of the education in America. In the author’s vision, the history is constituted by unexpected events that interrupt processes. So much the event as the action generates discontinuities and, therefore, they don’t recognize any cause in the strict sense of the term. This text presents reflexions about the theme of the appearance; emphasizes the condition of being alive means to have an impulse of auto-exposition that corresponds to the quality to appear of each one. Appear means to be noticed by the other ones, changing by the spectator interest. About the educational subject, Arendt affirms that in face of the world that must be continually organized, the education performs a central function. It’s very important that the men that live in the world not obstruct the new generations in their futures .The course of this investigation makes possible to affirm that Arendt recuperates the understanding that the human capacity inaugurates something new, that cannot be predict and that corresponds to the own political action for excellence.
Keywords: Ação; Política; História; Educação; Aparência; Totalitarismo; Action; Politic; History; Education; Appearance; Totalitarian system; ACCNPQ::Ciências Humanas::Filosofia